School Culture dan Procedural Justice terhadap Counterproductive Behaviour Pada Preservasi Lingkungan Peserta Didik di SMAN Jakarta - Cynthia Loka (IJEEM - Indonesian Journal of Environmental Education and Management, 2022)
Environmental problems are always increasing every day where one of the contributing factors is humans. Counterproductive behavior towards environmental preservation occurs due to someone's ignorance about the important role of the environment for life. This study aims to determine the effect of school culture and procedural justice on students' counterproductive behaviour. This research was conducted at SMAN 21 Jakarta in August - December 2022 with a research sample of 75 students. The research method used is a causal survey method and is analyzed using path analysis. The results of this study indicate that (1) school culture has a direct effect on procedural justice significantly by 0.762, (2) procedural justice has a direct effect on counterproductive behaviour significantly by 0.152, (3) school culture has a direct effect on counterproductive behaviour not significantly by 0.035, and (4) there is no indirect effect of school culture on counterproductive behaviour through procedural justice.